A Uniform Semantics for Declarative and Interrogative Complements. (5th July 2018) - Theiler, Nadine; Roelofsen, Floris; Aloni, Maria
Abstract: This paper proposes a semantics for declarative and interrogative complements and for so-called responsive verbs, like know and forget, which embed both kinds of complements. Following Groenendijk & Stokhof (1984), we pursue a uniform account in the sense that we take both kinds of complements to be of the same semantic type and we assume a single lexical entry for each responsive verb. This approach avoids a number of problems for non-uniform theories, such as the reductive theories of Karttunen (1977), Heim (1994), Lahiri (2002), Spector & Egré (2015), among others, and the twin relations theory of George (2011) . On the other hand, our account also addresses the main limitation of Groenendijk & Stokhof's (1984) proposal, which is that it is primarily designed to derive strongly exhaustive readings for interrogative complements. Our account is more flexible in that it straightforwardly derives non-exhaustive and intermediate exhaustive readings as well.